Analysis of Interest in Learning Arabic in Class VIII at Junior High School in Sidoarjo Regency - Juriani Eka Ariana; Doni Septi (Universitas Muhammadiyah Sidoarjo, 2022)
Research objectives: a. To find out the interest in learning Arabic in class VIII students at SMP Muhammadiyah 5 Tulangan b. To find out what methods are applied by teachers in increasing students' interest in learning Arabic. c. Factors that influence students' interest in learning Arabic. This type of research is qualitative by utilizing data collection techniques in the form of, a. Observation b. Interview c. Documentation d. Questionnaire. Data analysis was carried out using data collection analysis, data reduction, data presentation, and drawing conclusions or verification. Where the validity of the data is tested by triangulation, namely triangulation of sources, triangulation of techniques, triangulation of time as well as extension of observations and increasing persistence. The results showed that the analysis of students' interest in learning Arabic in class VIII at SMP Muhammadiyah 5Tulangan concluded that students' interest in learning Arabic in learning Arabic was quite high, seen from the results of the data through a questionnaire that was processed through the SPSS tool which revealed the average student interest in learning Arabic. high enough. This is evidenced by the attention of students in receiving good Arabic lessons, paying attention to the teacher who is explaining in an orderly manner and following the Arabic lesson to completion and doing the tasks given by the teacher according to the time determined by the teacher. So that the enthusiasm for learning Arabic is formed which tends to be high.